Geomorphological Compartmentation of Pereiro Massif and its surroundings, in Northern Northeast of Brazil - Albuquerque, Diêgo Souza; Xavier, Rafael Albuquerque; Suertegaray, Dirce Maria Antunes (Revista Brasileira de Geomorfologia, 2024)
The Pereiro Massif (PM), located between the states of Ceará, Rio Grande do Norte and Paraíba, is a granitoid body that occupies an area of ​​approximately 2,200 km2, and and has maximum altitudes of 861 meters. This work aimed to elaborate and discuss the geomorphological compartmentalization of the Pereiro Massif and its surroundings. To this end, the following procedures were followed: 1) bibliographic and cartographic review on the geology and relief of the study area; 2) creation of the geomorphological map in a GIS environment, through SRTM image processing; 3) field activities for mapping conference, obtaining information to characterize the shapes and photographic survey. Fifteen units were mapped and grouped into three dimensions that consider the resulting processes and forms: accumulation, flattening and erosion surfaces. The compartments are classified recognizing processes associated with continental denudation with erosion, transport and deposition of material, based on structural geomorphology. The mapping carried out enhances the scientific notoriety of the PM and is expected to serve for environmental planning actions, such as the creation of protected areas and environmental licensing procedures.